1991
DOI: 10.1111/j.1365-2621.1991.tb05300.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase as Blanching Index for Frozen Vegetable Soybeans

Abstract: Blanched samples of frozen vegetable soybeans using peroxidase (POD) and lipoxygcnase (LIP) as blanching indices were compared with unblanched samples during storage by sensory evaluation, vitamin C determination and remaining enzyme activity. Samples using LIP and POD as blanching indices showed no significant differences in sensory quality during 160-day frozen storage, while both treatments were significantly different from unblanched samples. Vitamin C in samplcs using LIP as blanching index was higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 12 publications
4
55
0
Order By: Relevance
“…This is consistent with a 90% reduction of POD activity that occurred after blanching vegetable soybeans for 1.14 min at 100°C water [26]. Blanching time and calcium chloride concentration had significant effects on enzyme inactivation.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This is consistent with a 90% reduction of POD activity that occurred after blanching vegetable soybeans for 1.14 min at 100°C water [26]. Blanching time and calcium chloride concentration had significant effects on enzyme inactivation.…”
Section: Resultssupporting
confidence: 73%
“…The supernatant was used as the crude enzyme extract. POD activity was measured using a spectrophotometric method as described by [26] with some modifications. POD substrate solution was prepared freshly by mixing 0.1 mL guayacol, 0.1 mL hydrogen peroxide (30%), and 99.8 mL potassium phosphate buffer (0.1 M; pH 6.5), and homogenizing for 30 s, followed by transferring 1 mL into a 1-cm cuvette.…”
Section: Peroxidase (Pod) Assaymentioning
confidence: 99%
“…Optimum pH for lipoxygenase activity depends on plant species: eggplant -pH 7.0 (López-Nicolás et al, 2001), sweet corn germ -pH 6.0-7.0 (Theerakulkait & Barrett, 1995), lupinus -pH 6.0-8.0 (Yoshie-Stark & Wäsche, 2004), soybean LOX-1 -pH 9, LOX-2 -pH 6.5 (Sheu & Chen, 1991). Gökmen, Bahceci, and Acar (2002) have reported that optimum pH for LOX obtained from green pea was at 6.0.…”
Section: Effect Of Ph On Enzyme Activitymentioning
confidence: 97%
“…Ramesh et al (2002) reported the results of using pulsed microwave to blanch spinach, carrot, and bell peppers at 95°C, and established the kinetics of POD inactivation. Sheu and Chen (1991) studied blanching vegetable soybeans prior to freezing using lipoxygenase (LIP) and POD (auxiliary index) as indices. Because heat-stable POD is inactivated slowly during thermal treatments, complete inactivation of POD can take a long time and hence may cause significant damage to the texture and colour of the fruit and vegetables.…”
Section: Introductionmentioning
confidence: 99%